An HLA-C amino-acid variant in addition to HLA-B*27 confers risk for ankylosing spondylitis in the Korean population. Issue 1 (December 2015) - Kim, Kwangwoo; Bang, So-Young; Lee, Seunghun; Lee, Hye-Soon; Shim, Seung-Cheol; Kang, Young; Suh, Chang-Hee; Sun, Celi; Nath, Swapan; Bae, Sang-Cheol; Kim, Tae-Hwan
Abstract Introduction The presence of theHLA-B*27 allele is a major risk factor for the development of ankylosing spondylitis (AS), which causes chronic inflammation of the spine and other sites. We investigated residual effects outsideHLA-B within the major histocompatibility complex (MHC) region in the Korean population. Methods Using the Korean HLA reference panel, we inferred the classic HLA alleles and amino-acid residues of the six HLA genes (HLA-A, -B, -C, -DPB1, -DQB1, and -DRB1 ) and MHC single-nucleotide polymorphisms in 3820 Korean subjects, including 654 Korean cases of AS and 3166 controls, who were genotyped by using Immunochip. Logistic regression and log-likelihood ratio tests were used in AS association tests for imputed markers. Results The most significant associations were identified at amino-acid positions in the epitope-binding site of HLA-B (P  = 1.71 × 10−481 at position 70, P  = 7.20 × 10−479 at position 97, andP  = 2.54 × 10−484 at positions 114), highlighting the risk effect of theHLA-B*27 allele and the protective effects of other classic alleles. A secondary effect was located at the leucine at amino-acid position 116 in the epitope-binding site of HLA-C (P  = 1.69 × 10−14 ), completely tagging theHLA-C*15:02 allele. This residue had a large effect inHLA-B*27 -negative patients (odds ratio = 6.6, 95 % confidence interval = 3.8 to 11.4). Conclusions The four amino-acid positions of HLA-B and -C account for most of the associations between AS and MHC in the Korean population. This finding updates the list of AS susceptibility loci and provides new insight into AS pathogenesis mediated by MHC class I molecules.